2019
DOI: 10.1039/c8nr05860a
|View full text |Cite
|
Sign up to set email alerts
|

The fate of cellulose nanocrystal stabilised emulsions after simulated gastrointestinal digestion and exposure to intestinal mucosa

Abstract: The intestinal mucus layer prevents cellulose nanocrystals from reaching the epithelium and can modulate lipid and bile absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…Experiments on gastrointestinal mucus that has been detached from tissue are useful for evaluating the influence of luminal compounds (e.g. type of drug and/or drug carrier 1921 , type of dietary fibre 22,23 , etc.) or the source of mucus (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments on gastrointestinal mucus that has been detached from tissue are useful for evaluating the influence of luminal compounds (e.g. type of drug and/or drug carrier 1921 , type of dietary fibre 22,23 , etc.) or the source of mucus (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, Pickering emulsion based delivery systems have been used for encapsulation and controlled release applications in various fields such as cosmetic, food, biomedical, and pharmaceutics . For instance, Mackie et al have produced sunflower (O/W) emulsions stabilized by CNCs, which were exposed to stimulated upper gastrointestinal tract digestion (Mackie et al, 2019). They demonstrated that CNCs were entrapped in the intestinal mucus layer and failed to reach the underlying epithelium, leading to the decrease of the adsorption of saturated lipids, thus concluded the effectiveness of CNC emulsifier through the reduction of plasma cholesterol.…”
Section: Nanocellulose As Pickering Emulsifiersmentioning
confidence: 99%
“…Recent advancements in nanotechnology have provided unique opportunities in the field of drug development programs. Nanoparticles are known as major products of the nanotechnologies with at least one dimension of 100 nm or less, and have attracted great interest due to their intriguing and unique properties compared to their bulk material [10, 11]. These characteristics make them suitable for different biomedical applications such as drug delivery, medical diagnostics and therapeutics [12].…”
Section: Introductionmentioning
confidence: 99%